Pengaruh Kompetensi, Motivasi, Kepemimpinan, dan Lingkungan Kerja Terhadap Manajemen Stres dan Kinerja Karyawan pada Dinas - Udisubakti Ciptomulyono; M. Yusak Anshori; Aldo Fodyansa (Jurnal Bisnis dan Keuangan, 2017)
This research conducted by background of “X” Agency East Java Province as one of the biggest agencies with the highest number of employees in East Java and has a very broad work scope because it is a merged from some sub agencies before. Various social issues of East Java governance in 2015 became the main task of “X” Agency East Java Province to be completed. In order to fulfill their roles, responsibilities, and functions as the government agencies that serve people, all employees in “X” Agency East Java Province are required to be able to have optimal performance. This study aimed to analyze factors that can affect the performance of employees so can provide feedback to “X” Agency East Java Province in terms of corrective measures to be taken in the future in order to always have optimal performance. This study used partial least squares analysis through SmartPLS 3.0 program. Independent variables analyzed in this study were competence, motivation,leadership, and work environment towards dependent variable thus stress management and employee performance. Random sampling taken at 160 employees of “X” Agency East Java Province. Data collection process conducted by questionnaires distribution. The result showed that only competence and work environment has a significant effects on stress management, while stress management itself and competence also have a significant effects on employee performance. Other variables that is motivation and leadership does not have a significant effects on the dependentvariable stress management and employee performance. Suggestion for improvement are given to the “X” Agency East Java Province at the end of the study in order to further improve their performance.